The arctic patrol mystery - Dixon, Franklin W. (New York, Grosset & Dunlap, 1969)
While searching in Iceland for a missing sailor sought by an insurance company, the teen-age detective brothers uncover a plot threatening the life of a United States astronaut and the secrets of NASA$1 (Bs moon project.s
Keywords: Mystery and detective stories